A redescription of Acanthinozodium odem (Levy, 2007) comb. nov. (Araneae, Zodariidae), with first description of the male - Zonstein, Sergei (Zootaxa, 2025)
Zodarion odem Levy, 2007 is redescribed and transferred from Zodarion Walckenaer, 1826 to Acanthinozodium Denis, 1966; the male of this species is described for the first time. Among the members of the latter genus, Acanthinozodium odem (Levy, 2007) comb. nov. is distinguishable by a peculiar structure of the female copulatory organs, while the structure of the male palp in the considered species appears to be practically identical to that in some other congeners. In view of the newly received data, Acanthinozodium embraces 25 species; the genus is recorded for the first time in Israel, as well as in the entire Eastern Mediterranean region.